Magnetism of metal-nitroxide compounds involving bis-chelating imidazole and benzimidazole substituted nitronyl nitroxide free radicals - Luneau, Dominique; Rey, Paul (Coordination chemistry reviews, 2005)
Coordination compounds based on imidazole and benzimidazole substituted nitronyl nitroxide radicals with transition metal ions and trivalent lanthanide ions are described from the perspective of their magnetic properties. For the transition metal compounds the crystal structures show various metal-nitroxide dimensionalities including mononuclear (0D), one-dimensional (1D) and two-dimensional (2D) complexes. The mononuclear complexes were isolated with most metal ions of the first transition series. One copper(II) complex shows a copper(II)–radical ferromagnetic coupling ( J = +75 cm −1) while for the other mononuclear compounds, mainly with manganese(II), the metal–radical interactions are antiferromagnetic. The one-dimensional and two-dimensional complexes are manganese(II) compounds which show canting effects leading to weak ferromagnetism. For the trivalent lanthanide ions [La(III), Gd(III) and Eu(III)], three series of mononuclear complexes were obtained in which the metal center is bound to four, two or one nitroxide radicals depending on the counter ions and ancillary ligands. Unexpectedly, in most gadolinium(III) complexes, the Gd(III)–radical interactions were found to be antiferromagnetic in contradiction with other foundings and previous theoretical models. In support to the magnetic studies, the optical properties of the lantanide complexes have also been investigated and are briefly described.